Pengaruh Model Role Playing Berbantuan Media Boneka Tangan Terhadap Ketrampilan Berbicara Pada Kelas IV SD Negeri Surodadi 3 Candimulyo - Dwi Puji Lestari (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
This study aims to determine students' speaking skills through learning role playingmodels assisted by hand puppet media to fourth grade students at SD Negeri Surodadi 3Candimulyo.This study uses a pre-experimental type one group pretest posttest. Samplingin this study used a saturated sampling technique. The method of data collection is doneby using a performance appraisal technique. The validation test of the performanceassessment instrument was carried out using expert validation. Analysis of the data usedin this study using parametric statistical techniques, namely the Paired Sample T-Testtest with the help of the IBM SPSS statistic 22 application program for window. The resultsof data analysis using the Paired Sample T-Test obtained a value of Sig (2-tailed) < 0.005.Based on the results of data analysis, the average pretest value was 53 while the posttestvalue was 63 with an average difference of 10. From the results of the study, it can beconcluded that the use of role playing learning models assisted by hand puppet media hasan effect on students' speaking skills.